?Evaluation of Pakistani Sweet Basil Oil for Commercial Exploitation - Khatri, L.M.; Nasir, M.K.A.; Saleem, R.; Noor, F. (Biological Sciences - PJSIR, 1995)
tified by comparison with their standard samples in the GC and fragmentation pattern of the individual component in the mass spectra [5-6]. The percentage composition was found by gas chromatography on the basis of peak areas. The compounds of lower content (less than 0.1%) were not identified